2020
DOI: 10.1111/sms.13740
|View full text |Cite
|
Sign up to set email alerts
|

Health problems in youth competitive alpine skiing: A 12‐month observation of 155 athletes around the growth spurt

Abstract: Alpine ski racing is known as a high‐risk sport; however, little is known on the health problems occurring at youth level. The purpose of this study was to investigate the prevalence of health problems in youth competitive alpine skiers with respect to sex, age, and season differences, to describe their severity and location and to assess the influence of biological maturation. Over a 12‐month period, 155 youth competitive alpine skiers around the growth spurt were prospectively monitored for health problems u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
47
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 28 publications
(51 citation statements)
references
References 41 publications
3
47
1
Order By: Relevance
“…Despite these plausible sports-related adverse loading patterns, only a few studies, however, have investigated the occurrence of lower back complaints in competitive alpine skiers. Moreover, due to focusing on a different age group and reporting other time prevalence measures or absolute injury rates, most of them are not directly comparable to the results of the current study [3,4,6,8,11]. The only study directly comparable to our investigation reported similar magnitudes of current low back pain (67.0%) in ski high school athletes aged 15-19 years [30].…”
Section: Prevalence Of Lower Back Complaints With Respect To Sex Catcontrasting
confidence: 71%
See 2 more Smart Citations
“…Despite these plausible sports-related adverse loading patterns, only a few studies, however, have investigated the occurrence of lower back complaints in competitive alpine skiers. Moreover, due to focusing on a different age group and reporting other time prevalence measures or absolute injury rates, most of them are not directly comparable to the results of the current study [3,4,6,8,11]. The only study directly comparable to our investigation reported similar magnitudes of current low back pain (67.0%) in ski high school athletes aged 15-19 years [30].…”
Section: Prevalence Of Lower Back Complaints With Respect To Sex Catcontrasting
confidence: 71%
“…Conversely, the frequency of lower back complaints lasting more than two weeks changed from 3.3% in the off-season to 21.3% in the period of the competition season. This fact may suggest that more severe lower back complaints emerge from skiing rather than from off-snow training [3].…”
Section: Prevalence Of Lower Back Complaints With Respect To Sex Catmentioning
confidence: 99%
See 1 more Smart Citation
“…With respect to overuse injuries, the knees (and especially the patella tendon) are most affected in both youth and elite skiers. [9][10][11] A major concern pertains to youth skiers around the growth spurt, whose bodies are still maturing and, therefore, are especially sensitive to unfavourable loads. 11,12 Moreover, in under 16 years old (U16) skiers, overuse injuries revealed to be more frequent in females than in males.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 Moreover, in under 16 years old (U16) skiers, overuse injuries revealed to be more frequent in females than in males. 9 In skiing, up to 1.75 times the body weight can act on each leg, 13 and the knee joint is inevitably subjected to extreme kinematics, including high degrees of flexion and valgus. 14 In addition, due to uneven or bumpy snow surfaces and the chattering of the skis when interacting with the snow surface while turning, skiers are typically exposed to high vibration loads and impact-like shocks, that are partially attenuated by the knee joint and the perturbation-induced activation of its stabilizing muscles.…”
Section: Introductionmentioning
confidence: 99%